2018
DOI: 10.1038/s41419-018-1235-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: FOXM1 modulates 5-fluorouracil sensitivity in cholangiocarcinoma through thymidylate synthase (TYMS): implications of FOXM1–TYMS axis uncoupling in 5-FU resistance

Abstract: Fluorouracil (5-FU) is the first-line chemotherapeutic drug for cholangiocarcinoma (CCA), but its efficacy has been compromised by the development of resistance. Development of 5-FU resistance is associated with elevated expression of its cellular target, thymidylate synthase (TYMS). E2F1 transcription factor has previously been shown to modulate the expression of FOXM1 and TYMS. Immunohistochemical (IHC) analysis revealed a strong correlated upregulation of FOXM1 (78%) and TYMS (48%) expression at the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…The prognosis of patients with recurrent or refractory OS is extremely poor, 2,11 highlighting the urgent need for more effective treatments of this grievous malignancy. In the present study, we found that FoxM1, a biomarker for a poor prognosis in many malignancies, [12][13][14][15] is upregulated in human OS tissues and MG-63 or HOS-MNNG cell lines. These data are consistent with previous reports showing that FoxM1 is overexpressed in a large set of human OS tissues.…”
Section: Discussionsupporting
confidence: 55%
“…The prognosis of patients with recurrent or refractory OS is extremely poor, 2,11 highlighting the urgent need for more effective treatments of this grievous malignancy. In the present study, we found that FoxM1, a biomarker for a poor prognosis in many malignancies, [12][13][14][15] is upregulated in human OS tissues and MG-63 or HOS-MNNG cell lines. These data are consistent with previous reports showing that FoxM1 is overexpressed in a large set of human OS tissues.…”
Section: Discussionsupporting
confidence: 55%
“…Next, we investigated loss-of-function (LOF) and gain-of-function (GOF) events of key enzymes of the pyrimidine metabolic pathways. TYMS is considered as the key therapeutic target for 5-FU and overexpression of its gene has been linked to 5-FU resistance in in vitro as well as in in vivo experiments (Watson et al 2010;Intuyod et al 2018). TYMS showed no LOF mutations in the breast and colorectal cohort, supporting the findings that TYMS is an essential gene (Blomen et al).…”
Section: Impact On Tumorigenesissupporting
confidence: 54%
“…Western blot analysis: For western blot, whole-cell lysate of cells were prepared using RIPA buffer [20 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1 mM Na 2 EDTA, 1 mM EGTA, 1% NP-40, 1% sodium deoxycholate, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate, 1 mM Na3VO4 and 1 μg/mL leupeptin] as previously described 12 . The lysed samples were collected after centrifugation for 15 min at 12,000 × g, 4°C.…”
Section: Transwell-migration and Invasion Assaymentioning
confidence: 99%
“…Chromatin immunoprecipitation assay (ChIP): Chromatin immunoprecipitation was performed as previously described with minor modifications 12 . (See also Supplementary Materials and Methods).…”
Section: Transwell-migration and Invasion Assaymentioning
confidence: 99%